Development of a multi-level family planning intervention for couples in rural Uganda: key findings & adaptations made from community engaged research methods - Christine Muhumuza; Katelyn M. Sileo; Rhoda K. Wanyenze; Trace S. Kershaw; Haruna Lule; Samuel Sekamatte; Susan M. Kiene (BMC, 2023)
Abstract Background Uganda has among the highest fertility rates in the world and multi-level barriers contribute to the low contraceptive use. Objective The objective of this study was to develop a culturally and socially relevant, community-based intervention to increase contraceptive use among couples in rural Uganda through community-engaged research methods. This study reports on the community-engaged research that informed the intervention's content and structure and the final content of the intervention; the evaluation of the pilot intervention will be reported upon completion. Methods An intervention steering committee of community stakeholders reviewed the initially proposed intervention content and approach. Four (4) gender-segregated focus groups were conducted with twenty-six (26) men and women who had an unmet need for family planning. Fifteen key-informant interviews were conducted with community leaders and family planning stakeholders. Finally, the 4-session intervention was pilot tested with a cohort of couples (N = 7) similar in demographics to the target sample of the future pilot intervention trial. Qualitative data were analyzed thematically. Results Findings included the identification of community beliefs to reshape in order to increase family planning acceptance, as well as strategies to engage men, acceptable approaches for community leader involvement in the intervention to endorse family planning, and methods for managing gender dynamics and minimizing risk of unintended negative consequences of participation. The findings were used to inform the ideal structure and format of the intervention, including the distribution of contraceptives directly during group sessions, and identified the need to strengthen health worker capacity to provide Long-Acting Reversable Contraceptives (LARCs) as part of the intervention. Conclusions These findings were used to refine an intervention before a larger scale pilot test of its feasibility, acceptability, and potential efficacy. They can inform other multi-level family planning interventions in similar settings and the methods can be adopted by others to increase the feasibility, acceptability, and cultural relevance of interventions.